Type 1 diabetes in older adults: Comparing treatments and chronic complications in the United States T1D Exchange and the German/Austrian DPV registries. (December 2016) - Weinstock, Ruth S.; Schütz-Fuhrmann, Ingrid; Connor, Crystal G.; Hermann, Julia M.; Maahs, David M.; Schütt, Morten; Agarwal, Shivani; Hofer, Sabine E.; Beck, Roy W.; Holl, Reinhard W.
Highlights: Study of T1D adults ≥60 years in the US and German/Austrian. Individuals in both registries were similar in BMI, percent with obesity, and gender. Greater use of antihypertensives, statins and insulin pumps in the US. Fewer chronic complications in the US. Further research is needed to improve outcomes in older adults with T1D. Abstract: Aims: Compare characteristics, therapies and clinical outcomes in older adults with type 1 diabetes in the United States T1D Exchange (T1DX) and German/Austrian Diabetes Patienten Verlaufsdokumentation (DPV) registries. Methods: Cross-sectional study of adults ≥60 years old with type 1 diabetes seen in 2011–2012 in the T1DX ( n = 1283) and DPV ( n = 2014) registries. Wilcoxon rank-sum test was used for continuous variables and chi-square test for categorical variables. Adjusted analyses used generalized linear models. Results: Individuals in both registries were similar in body mass index (mean 27 kg/m 2 ), percent with obesity (25%) and gender (48% male). In T1DX there was longer diabetes duration (32.3 vs. 28.8 years), greater use of antihypertensive medications (including ACE-I and ARBs; 85% vs. 62%), statins (68% vs. 40%), aspirin (77% vs. 21%), insulin pumps (58% vs. 18%), and less smoking (7% vs. 10%); lower adjusted mean LDL-cholesterol (84 vs. 109 mg/dL), and lower adjusted mean systolic and diastolic blood pressures (128 vs. 136 and 68 vs. 74 mmHg); fewer myocardial infarctions (6% vs. 9% [99% CI of difference, 1% to 5%]), strokes (2% vs. 8% [3% to 7%]), microvascular complications including microalbuminuria (17% vs. 44% [22% to 32%]) but increased depression (16.1% vs. 8.7%). Adjusted mean HbA1c levels were similar (7.5%, 58 mmol/mol). Conclusions: Differences between the registries included greater use of antihypertensives, statins and insulin pumps, and fewer chronic complications in the T1DX. Further research is needed to better understand the role of intensive therapy in improving outcomes in older adults with type 1 diabetes.